Analisis Perbandingan Pendeteksi Sarana Pada Lintas Surabaya - Madiun - Puspitasari, Mariana Diah; Purwaka, Faris Hendra (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
One example of technological developments in signaling systems in Indonesia is the use of detection facilities on rail lines. A detector is a device that functions to detect the presence or absence of train facilities on the railroad track. Detection equipment is divided into two types, namely axle counter and track circuit. Track circuit detects the presence of trains on the rails, while the axle counter functions to count train axles. This study aims to find a detection system for facilities that is suitable and in accordance with the conditions of the Surabaya-Madiun cross and find out the characteristics for the installation of detection facilities in accordance with the pathway. To find out the appropriate facility system, the two tools are analyzed in terms of system reliability, environmental influences, advantages and disadvantages, disruptions, maintenance, and operations. The results showed that an effective and efficient way of detecting traffic in Surabaya - Madiun was the detection of a double head axle counter facility. This tool is very suitable to be installed in the emplacement.